Role of the IFN I system against the VHSV infection in juvenile Senegalese sole (Solea senegalensis) - Alvarez-Torres, Daniel (Vet Res, 2016)
Senegalese sole is susceptible to marine VHSV isolates but is not affected by freshwater isolates, which may indicate differences regarding virus-host immune system interaction. IFN I induces an antiviral state in fish, stimulating the expression of genes encoding antiviral proteins (ISG). In this study, the stimulation of the Senegalese sole IFN I by VHSV infections has been evaluated by the relative quantification of the transcription of several ISG (Mx, Isg15 and Pkr) after inoculation with marine (pathogenic) and freshwater (non-pathogenic) VHSV isolates. Compared to marine VHSV, lower levels of RNA of the freshwater VHSV induced transcription of ISG to similar levels, with the Isg15 showing the highest fold induction. The protective role of the IFN I system was evaluated in poly I:C-inoculated animals subsequently challenged with VHSV isolates. The cumulative mortality caused by the marine isolate in the control group was 68%, whereas in the poly I:C-stimulated group was 5%. The freshwater VHSV isolate did not cause any mortality. Furthermore, viral RNA fold change and viral titers were lower in animals from the poly I:C + VHSV groups than in the controls. The implication of the IFN I system in the protection observed was confirmed by the transcription of the ISG in animals from the poly I:C + VHSV groups. However, the marine VHSV isolate exerts a negative effect on the ISG transcription at 3 and 6 h post-inoculation (hpi), which is not observed for the freshwater isolate. This difference might be partly responsible for the virulence shown by the marine isolate.